2016
DOI: 10.1111/jce.13084
|View full text |Cite
|
Sign up to set email alerts
|

miRNAs Regulate hERG

Abstract: Expression and functions of hERG are regulated by specific miRNAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 47 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…Previous study has shown that a kind of cells expressing high level of the fatty acid receptor CD36 has been found in human oral cancer samples, and they have a high metastatic potential in mice [34]. miRNAs play an important regulatory role in post-transcriptional regulation of gene expression, and participate in a variety of biological processes including intercellular signal transmission, cell proliferation, growth, differentiation, apoptosis, and cell metabolism [35]. Recent studies have found that miRNA plays an important role in energy metabolism such as glucose metabolism, fat metabolism and amino acid metabolism [36, 37].…”
Section: Discussionmentioning
confidence: 99%
“…Previous study has shown that a kind of cells expressing high level of the fatty acid receptor CD36 has been found in human oral cancer samples, and they have a high metastatic potential in mice [34]. miRNAs play an important regulatory role in post-transcriptional regulation of gene expression, and participate in a variety of biological processes including intercellular signal transmission, cell proliferation, growth, differentiation, apoptosis, and cell metabolism [35]. Recent studies have found that miRNA plays an important role in energy metabolism such as glucose metabolism, fat metabolism and amino acid metabolism [36, 37].…”
Section: Discussionmentioning
confidence: 99%
“…The ether-a-go-go-related gene (hERG) is the major molecular component of the rapidly activating delayed rectifier K + current (Ikr) and it is also modulated by miRNAs in LQTS. By coupling in silico and in vitro studies, Lian et al correlated miR-134, miR-103a-1, miR-143, and miR-3619 overexpression with the downregulation of hERG mRNA and protein [67]. Moreover, the current activation and tail amplitude of hERG channel was reduced upon the increase of miR-103a-1 levels.…”
Section: Mirnas and Inherited Cardiomyopathiesmentioning
confidence: 99%